PENGARUH METODE EKSPERIMEN TERHADAP KESADARAN SISWA TENTANG KEBERSIHAN LINGKUNGAN DALAM PEMBELAJARAN IPAS DI KELAS IV SD - Fadlani, Zahratul; Sumianto; Mufarizuddin; Syahrul Rizal, Muhammad; Fitra Surya, Yenni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the experimental method on students' awareness of environmental cleanliness in IPAS (Integrated Natural and Social Sciences) learning in Grade IV at SDN 003 Bangkinang. The research was motivated by the low level of students’ awareness in maintaining school cleanliness, such as littering, neglecting class duties, and showing little care for classroom facilities. The research method used was a quasi-experimental design with the Non-Equivalent Control Group Design. The sample consisted of two classes: Class IV A as the control group and Class IV B as the experimental group. The experimental class was taught using the experimental method, while the control class used the lecture and discussion method.The research instruments included tests (pretest and posttest), questionnaires, and observations. The results showed that the posttest average score of the experimental class was higher than that of the control class. The average posttest score for the experimental class was 87.56, while the control class scored 75.56. Moreover, the questionnaire results indicated a significant improvement in environmental cleanliness awareness among students in the experimental class after the implementation of the experimental method. Based on the t-test, the significance value (2-tailed) was less than 0.05, indicating a significant difference between the experimental and control classes. Therefore, it can be concluded that the experimental method has a significant effect on increasing students’ environmental cleanliness awareness in IPAS learning in Grade IV at SDN 003 Bangkinang. Keywords: Experimental Method, Environmental Cleanliness Awareness, IPAS, Elementary School.